Study of Palmar Dermatoglyphics in Cataract Associated with Diabetes Mellitus in Central India Region - Shriram Dhule, Dr. Pankaj; Paliwal, Dr. Rahul Omprakash (International Journal of Innovative Research in Medical Science, 2018)
Objective: to study finger and palmar dermatoglyphic patterns in diabetic cataract patients, to find out whether a specific dermatoglyphic trait exists & its significance, To compare dermatoglyphic configuration of diabetic cataract patients with normal population in central India region. Material & methods: The sample constituted 200 (100 men and 100 women) patients suffering from cataract associated with diabetes mellitus, all above 40 years of age group obtained from Ophthalmology wards, of a government medical college, in central India. The age matched control group of 200 (100 men and 100 women) were obtained from general population which were normal healthy individuals with no other obvious genetic disorders, all above 40 years of age group. Dermatoglyphic prints were taken by ‘INK METHOD’ described by Cummins (1936)[4] and Cummins and Midlo (1961) & were subjected for detail dermatoglyphic analysis with the help of magnifying hand lens. The prints obtained by ink method were studied in right and left hand separately. For statistical analysis of qualitative data 2 x 2 chi-square test and for quantitative data student’s t-test were applied. Observation & results: Increase in total finger ridge count (TFRC) and absolute finger ridge count (AFRC) in cataract patients of both the sexes. Increase in frequency of loops in female cataracts, also male cataracts shows slight increase in loops. The increase in right hand is more prominent than that of left hand in both the sexes. Whorls pattern is decreased in right hand of female diabetics. The arch pattern found significantly higher in diabetic cataract males while it is lower in diabetic cataract females. Conclusion: Significant variations are observed in the various dermatoglyphic parameters among normal population and persons having cataract associated with diabetes mellitus. On the basis of results obtained, the study can be used for early detection of the predisposed persons from the normal population so that they can be subjected to preventive measures, to avoid the future burden of the disease on the community.